#1. x = - (2y) / (1-y)
#2. x = (-4y-3)/(1-y)
I can't really see the other questions, so I only did the first two. Hope this helps!
Answer:
x
+
2
y
−
9
Step-by-step explanation:
Answer:
-4x + y + 6z
Step-by-step explanation:
Combine like terms (Terms with the same variable):
(2x + 5y - z) + (-6x - 4y + 7z)
Add straight across:
2x - 6x = -4x
5y - 4y = y
-z + 7z = 7z - z = 6z
-4x + y + 6z is your answer.
~
Answer:
4t
Step-by-step explanation:
All we are doing is combining like terms and since all of then have a "t" in it we would just add the 4 "t's" together like normal addition.
Answer:h=−5t2−10t+70
Step-by-step explanation:
<!>BRAINLIEST APPERICATED<!> :D